A Study of the Effect of Grouting with Cement Kiln Dust (CKD) on the Shear Strength of Coastal Sandy Soils - فياض, توفيق; العبده, رامي; السقر, فاتن (Latakia University Journal -Engineering Sciences Series, 2021)
Recently; many researches have focused on the utilization of industrial solid waste to improve weak soils. Because of their threat to the environment and public health, one of these waste is cement kiln dust (CKD) which is produced in large quantities during the manufacture of ordinary Portland cement. In this paper, we present a study on the effect of (CKD) grouts on the shear strength of sandy soils in the coastal region, to achieve the object of this research, we designed and fabricated a laboratory grouting model that simulates grouting site process. The soil was grouted with a suspension consisting of different percentages of cement kiln dust (2,4,6,8,10,12)% as a ratio of dry weight of the treated soil, and different mixing ratios (Water:CKD) (W:C=2:1, 4:1,6:1,8:1,10:1), we conducted a laboratory study on sandy soil before and after grouting treatment. The results proved the efficiency of using grouting cement kiln dust (CKD) to improve the shear strength of sandy soils in the coastal region, as the values of both shear strength and cohesion of grouted soil increase with increasing the (CKD) percentage and curing period, but they decrease when the (W:CKD) ratio increases. While the values of internal friction angle increase when the percentage of (CKD),curing period, and (W:C) ratio increase.